1996
DOI: 10.1002/j.1460-2075.1996.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of inhibition of DNA gyrase by the coumarins and the cyclothialidines revealed by X-ray crystallography.

Abstract: This study describes the first crystal structures of a complex between a DNA topoisomerase and a drug. We present the structures of a 24 kDa N‐terminal fragment of the Escherichia coli DNA gyrase B protein in complexes with two different inhibitors of the ATPase activity of DNA gyrase, namely the coumarin antibiotic, novobiocin, and GR122222X, a member of the cyclothialidine family. These structures are compared with the crystal structure of the complex with an ATP analogue, adenylyl‐beta‐gamma‐imidodiphosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
311
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(331 citation statements)
references
References 46 publications
14
311
0
Order By: Relevance
“…Analysis of the X-ray structure of the SaGyrB(1±234)± cyclothialidine binary complex as well as comparison with the E. coli p24±novobiocin complex revealed two regions for which there was no electron density. In the E. coli complex, electron density is lacking for the N-terminal 13 amino acids and the loop comprising residues 99±118 is disordered (Lewis et al, 1996). In the NgyrB±ADPNP complex, this glycine-rich loop forms a lid over the ATP-binding site, but in the p24± novobiocin complex it is not involved in ligand interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the X-ray structure of the SaGyrB(1±234)± cyclothialidine binary complex as well as comparison with the E. coli p24±novobiocin complex revealed two regions for which there was no electron density. In the E. coli complex, electron density is lacking for the N-terminal 13 amino acids and the loop comprising residues 99±118 is disordered (Lewis et al, 1996). In the NgyrB±ADPNP complex, this glycine-rich loop forms a lid over the ATP-binding site, but in the p24± novobiocin complex it is not involved in ligand interactions.…”
Section: Resultsmentioning
confidence: 99%
“…coumermycin and novobiocin) act by inhibiting ATP hydrolysis by the B subunit of DNA gyrase. The X-ray structure of the 43 kDa N-terminal fragment±AMPNP complex (NGyrB±AMPNP) and the 24 kDa N-terminal fragment±novobiocin complex of the gyrase B subunit from Escherichia coli have been described (Lewis et al, 1996;Wigley et al, 1991). The 24 kDa fragment of DNA gyrase has no inherent activity of its own; it has been shown to bind a novobiocin±Sepharose af®nity column with similar avidity to GyrB (Gilbert & Maxwell, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous structural analysis and kinetic studies of the aminocoumarin antibiotics have revealed critical interactions between the carbamoylated noviosyl ring and the ATP binding site of the gyrase B subunit (6)(7)(8). The strategy in the design of improved coumarin-based antibiotics is to maintain the noviose decorations necessary for binding while introducing additional functionalities to improve the inhibitory properties of the analog or modulate solubility.…”
Section: Discussionmentioning
confidence: 99%
“…This family of antibiotics exerts its antibacterial activity via the inhibition of the type II DNA topoisomerase DNA gyrase (2)(3)(4)(5). X-ray crystallographic analysis of a 24-kDa N-terminal fragment of DNA gyrase with bound novobiocin (6)(7)(8) or clorobiocin (9) reveals that the antibiotics bind competitively at the ATP site and that the aminocoumarin bicyclic ring is the scaffold for presenting the decorated L-noviosyl sugar moiety to the target enzyme.…”
mentioning
confidence: 99%
“…crystallographic examinations demonstrated that the aminocoumarin moiety and the substituted deoxysugar moiety are essential for the binding of these compounds to the B subunit of gyrase (Ali et al, 1993 ;Lewis et al, 1996 ;Maxwell, 1993 ;Tsai et al, 1997). The affinity of coumermycin A " for intact gyrase is extremely high : 50 % inhibition of gyrase is reportedly achieved by coumermycin A " in a concentration of only 0n004 µM, compared to 0n1 µM for novobiocin, 1n8 µM for norfloxacin and 110 µM for nalidixic acid (Peng & Marians, 1993).…”
Section: Abbreviations : Cid Collision-induced Dissociation ; Esi Ementioning
confidence: 99%